Successful management of acute respiratory failure in an Idiopathic Pulmonary Fibrosis patient using an extracorporeal carbon dioxide removal system - Vianello, Andrea; Arcaro, Giovanna; Paladini, Luciana; Iovino, Silvia (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Patients with Idiopathic Pulmonary Fibrosis (IPF) requiring Invasive Mechanical Ventilation (IMV) following unsuccessful treatment with Non-Invasive Ventilation (NIV) have a high mortality rate. IMV is, moreover, an independent predictor of poor outcome during the post-transplantation period in patients on waiting lists for Lung Transplantation (LT). Here we describe the successful management of an IPF patient with acute respiratory failure (ARF) using a pump-assisted veno-venous system for extracorporeal CO2 removal (ECCO2R) (ProLUNG® system) as an alternative to endotracheal intubation (ETI) following NIV failure. Given this positive experience, further studies are warranted focusing on the ECCO2R system’s tolerability, safety, and efficacy in patients with IPF and severe ARF in whom NIV alone is ineffective.